Conditions for the development of Polish agriculture in the context of globalization and European integration - Edyta Dworak; Maria Magdalena Grzelak (Comparative Economic Research. Central and Eastern Europe, 2015)
Developments in the global food economy and the increasing extent of globalization and trade liberalization pose new challenges for Polish agriculture. To meet these challenges it is essential for the agricultural and food industries to improve their competitiveness. This paper examines whether the funds allocated to Poland in the new budget perspective 2014-2020, and changes in the Common Agricultural Policy (CAP) as well as the increase in demand for food in developing countries will have a positive impact on the Polish agriculture and increase its competitiveness. The following issues will be examined:The financial framework of the EU budget, with particular emphasis on EU funds for agriculture and rural areas; The consequences of changes in the CAP; Analysis of the Rural Development Programme in Poland in the years 2014-2020; Analysis of the increase in demand for food in developing countries with large populations, The influence of transnational corporations on the control and formation of prices in the food sector.
Keywords: 330; Common Agricultural Policy; competitiveness of Polish agriculture; EU budget for 2014-2020; transnational corporations